Electricity consumption, thermal comfort and environmental impact of an educational institution located in the north of Argentina - Mendoza, Dora (2021)
The aim of this paper is to know the electricity consumption of an educational institution by the use of air conditioning equipment for thermal comfort, as well as the local and environmental impact that such consumption generates. The institution is located in the city of Orán (North of Argentina), in bioclimatic zone IIb (IRAM Standard 11603) and it is a University headquarters. For its operation it has 2 properties: property 1 is located in a downtown area and is the study unit. Applying different techniques and instruments is investigated about the climatic conditions of the region, the structural and functional aspects of the institution building, the dynamics of the educational community and its technological preferences for the achievement of thermal comfort, the electricity consumption in the period 2013-2018 and the areas of electricity demand. With all the data obtained and, applying a procedure based on reference months, the electricity consumption for the use of air conditioning equipment is estimated. Local impacts are also analyzed and the carbon footprint for this activity is estimated. The most important results are: it is a very hot region, the structural aspect of the building lacks bioclimatic concepts, the electricity consumption from the use of air conditioning equipment represents 28% of the total annual consumption of the property 1 and an approximate emission of 13 tnCO2eq / year, requiring between 1,300 and 2,600 trees for mitigation. It is essential to implement bioclimatic strategies in the building of the University Headquarters.